Alterations in plantar pressure after a protocol of neuromuscular fatigue in isoinertial machine - Rodriguez Perdomo, Leonardo; Rincón Yepes, Camilo Andres; Vargas Santiago, Miller Esneyder (SPORT TK-EuroAmerican Journal of Sport Sciences, 2021)
The objective of the present study sought to establish the differences presented in the plantar footprint after applying a neuromuscular fatigue protocol. A total of 10 healthy male athletes with an approximate age of 21 years were evaluated for the morphological component, with the Tanita BC585F® equipment (variables: weight Kg, fat KG, muscle Kg and bone Kg). In the fatigue protocol, the isoinertial Squat RSP® equipment was used. For the baropodometry test, both in the pre-test and in the post-test, the EcoWalk equipment was used. R-Type® pressure variables were taken for both feet, such as mean pressure, contact surface, anterior, posterior, right lateral and left lateral distribution. No significant differences were found in the pre and post test of the baropodometry test with a p> 0.05. Significant correlations were found between the morphological component and the baropodometry with a p <0.05.